PENURUNAN NON PERFORMING FINANCING BERBASIS ENTERPRISE RISK MANAGEMENT PADA BANK ISLAM DI INDONESIA - Fajar, Maulana; Mutamimah, Mutamimah (Jurnal Ekonomi dan Bisnis, 2023)
This research is proposed to identify the impact of the system of profit loss sharing and murabaha financing of Islamic banking on the value of non-performing financing and financial performance in the period 2010 - 2022. The research sample analyzed is the non merger Islamic public banking institutions in Indonesia which were taken using the purposive method. sampling with a total of 11 banks. The data analysis method used is quantitative analysis using panel data regression analysis techniques that combine cross section data with time series. From the results of the analysis conducted, it is evident that mudharabah financing has a positive impact on the NPF value. Musyrakah financing is proven to have a negative effect on the NPF value of Islamic banking. Murabaha financing is proven to have a negative effect on the NPF of Islamic banking. ERM is able to moderate mudharabah financing on NPF with moderation properties weakening the positive effect of mudharabah financing on NPF. ERM is able to moderate mudharabah financing on NPF with moderation properties strengthening the negative effect of mudharabah financing on NPF. ERM is able to moderate murabaha financing on NPF with moderation properties strengthening the negative effect of murabaha financing on NPF. NPF is proven to have a negative effect on the value of financial performance as measured by using the value of ROA.